Wild Atlantic cod sperm motility is negatively affected by ovarian fluid of farmed females - J Beirão (Inter-Research, 2014)
Atlantic cod escape from fish farms at higher rates than commonly cultured marine species, and escapees have been observed to interact with wild fish in mating aggregations. Previous research suggests that potential interbreeding is mediated largely by the likelihood of wild males spawning with escaped females, and as such, the egg and ovarian fluid characteristics of these females could affect fertilization success and the likelihood of hybridization. Farmed cod have been noted to have poor egg quality compared to wild individuals, and some of this difference may be due to the ovarian fluid, which can affect key sperm-motility parameters related to fertilization success. We tested the hypothesis that the ovarian fluid of farmed females negatively affects the sperm performance of wild males. Sperm-motility parameters and fertilization capacity of wild male sperm were analyzed in the presence of both farmed and wild female ovarian fluid. Sperm performed similarly in the presence of wild female ovarian fluid and a seawater control. Ovarian fluid of farmed females negatively affected sperm swimming and the capacity to fertilize eggs. These differences may be related to nutritional deficiencies of farmed individuals. Although it has been demonstrated that wild males actively court farmed females, our results indicate that their ovarian fluid quality can inhibit fertilization success.